Heterogeneous knowledge spillover channels in universities and green technology innovation in local firms: Stimulating quantity or quality? - Nie, Libing; Gong, Hong; Zhao, Danxiao; Lai, Xiuping; Chang, Mengyue (Frontiers in Psychology, 2022)
The sluggish status of green technology development has stimulated the search for new incentives and realization paths. Apart from the traditional regulatory-push and demand-pull approaches, we reposition the power of technology push. Based on the innovation diffusion theory, a multi-dimensional path model of knowledge spillover in universities is constructed, and the impact of heterogeneous knowledge spillover channels on green innovation activities of local firms is discussed. We find that R&D collaboration has a significant effect on the quality of green innovation of local firms, but not on the quantity of green innovation. In opposite, patent citations and technology transfer have unequal positive effects on the quantity of green innovation of local firms, while there is no evidence that they can also improve the quality of green innovation. Despite regional disparities, strict environmental regulations are pushing companies to cite university patents in some regions. University knowledge stock has largely contributed to both quantitative and qualitative advances in subsequent green innovation in local firms, with the beneficial effect on quality being stronger in firms with high absorptive capacity. Our conclusions provide a precise and objective evaluation of the impact mechanism of multiple knowledge spillover channels in universities on firms' green innovation, as well as a reference for the selection of the form of industry-university-research collaboration.